Fine-tuning Interaction between Aminoacyl-tRNA Synthetase and tRNA for Efficient Synthesis of Proteins Containing Unnatural Amino Acids - Wang, Nanxi (ACS Synth Biol, 2014)
[Image: see text] By using a directed evolution approach, we have identified aminoacyl-tRNA synthetase variants with significantly enhanced activity for the incorporation of unnatural amino acids into proteins in response to the amber nonsense codon in bacteria. We demonstrated that the optimization of anticodon recognition of tRNA by aminoacyl-tRNA synthetase led to improved incorporation efficiency that is unnatural amino acid-specific. The findings will facilitate the creation of an optimized system for the genetic incorporation of unnatural amino acids in bacteria.